Role of Increased Exercise Therapy Time in Stroke Rehabilitation - Muhammad Ali, Raja; Siddiqui, Muhammad Asadullah; Mail, Qaiser Jamal (Journal of Medicine, 2015)
Introduction: Stroke, is an important and well known cause of disability and physical impairment among adults all-over the world. The most commonly accepted treatment to rehabilitate patients with stroke is physiotherapy. The present review is an attempt to explain the impact of increased exercise therapy time (physical or occupational), compared to the normal duration of therapies in patients with stroke. Methods: We systematically searched electronic databases including Medline, Scopus, PubMed, CINAHL, and Cochrane to review published literaturein this area. Electronic searches have shown limited studies, which investigates the effects or no effects of increased duration of physiotherapy in patients following an attack of stroke. Articles, which reported on healthy participants i.e. people without stroke, were excluded. Also excluded were primary prevention studies, economic evaluations, and simple case reports. Results: A total of 175articles were identified using the keywords in the above mentioned databases. However, following the designedinclusion and exclusion criteria for this review only 11articles were included in this review. Conclusion: The result of this review supports the substantiate effectiveness of increased duration of exercise therapy among patients with stroke, as it has a favourable effect on activities of daily living. However, further research is needed in this area due to limited availability of high quality published evidence. J MEDICINE July 2015; 16 (2) : 105-111